Tafsir Ayat Al-Qur’an tentang Kewajiban Belajar-Mengajar: Analisis Tematik QS. al-‘Alaq (96) Ayat 1-5 - A. Nurul Muta’ali; Sulkifi; Nadila Putri; Fajar; Risma Handayani (Al-Kindi, 2026)
The first revelation of the Qur'an, QS. Al-‘Alaq verses 1-5, serves as the epistemological foundation of Islam, positioning intellectual activity as a primary priority. This article aims to deeply examine the obligation of teaching and learning through the lens of classical and contemporary interpretations. Employing a qualitative method with a library research approach, this study synthesizes various perspectives from exegetes such as Ibn Kathir, Ath-Thabari, Buya Hamka, and Quraish Shihab. The findings indicate that the command